3t-9=4(t+3)

Simple and best practice solution for 3t-9=4(t+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3t-9=4(t+3) equation:


Simplifying
3t + -9 = 4(t + 3)

Reorder the terms:
-9 + 3t = 4(t + 3)

Reorder the terms:
-9 + 3t = 4(3 + t)
-9 + 3t = (3 * 4 + t * 4)
-9 + 3t = (12 + 4t)

Solving
-9 + 3t = 12 + 4t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-4t' to each side of the equation.
-9 + 3t + -4t = 12 + 4t + -4t

Combine like terms: 3t + -4t = -1t
-9 + -1t = 12 + 4t + -4t

Combine like terms: 4t + -4t = 0
-9 + -1t = 12 + 0
-9 + -1t = 12

Add '9' to each side of the equation.
-9 + 9 + -1t = 12 + 9

Combine like terms: -9 + 9 = 0
0 + -1t = 12 + 9
-1t = 12 + 9

Combine like terms: 12 + 9 = 21
-1t = 21

Divide each side by '-1'.
t = -21

Simplifying
t = -21

See similar equations:

| 44+4y-16=15y-14-4y | | -3+13=12x-4-11x | | 5(x+2)=(x-7)+53 | | (16+2x)(12+2x)=396 | | 0=x^2/10+9x/10+11/5 | | 4x^2+44x-204=0 | | P(8)=25x^2-24x+615 | | y=-5x/6+50/3 | | 33/2= | | y=-40x+260 | | -.01g+60=0 | | -.01g+60=25 | | 3+8x=8x | | 5+4(x-7)=8-3(x-1) | | 4(23,245)^-1/3(13.4) | | 2d+14=50 | | 30/6/5=150/x | | (x^2+12x+36)/(x+7) | | 8-5x=12-(6x+7) | | 3x+7+7x=-37 | | 25w+0=500 | | 12x-(6x-12)=3+5x | | 2.52+7.25+5.38= | | -4x^2+2x+8=0 | | -7x^2+5x+5=0 | | -9x^2+148x-564=0 | | -5x^2+4x+5=0 | | 8v^2-18v+9=0 | | 3v^2-26v+35=0 | | 8+2x+-x^2=0 | | -2x^2+13x-18=0 | | 86.58+t=570.22 |

Equations solver categories